Sulfate-mediated Drought Tolerance in Maize Involves Regulation at Physiological and Biochemical Levels - Usmani, Muhammad Munir (Sci Rep, 2020)
Restriction in nutrient acquisition is one of the primary causes for reduced growth and yield in water deficient soils. Sulfur (S) is an important secondary macronutrient that interacts with several stress metabolites to improve performance of food crops under various environmental stresses including drought. Increased S supply influences uptake and distribution of essential nutrients to confer nutritional homeostasis in plants exposed to limited water conditions. The regulation of S metabolism in plants, resulting in synthesis of numerous S-containing compounds, is crucial to the acclimation response to drought stress. Two different experiments were laid out in semi-controlled conditions to investigate the effects of different S sources on physiological and biochemical mechanisms of maize (Zea mays L. cv. P1574). Initially, the rate of S application in maize was optimized in terms of improved biomass and nutrient uptake. The maize seedlings were grown in sandy loam soil fertigated with various doses (0, 15, 30 and 45 kg ha(−1)) of different S fertilizers viz. K(2)SO(4), FeSO(4), CuSO(4) and Na(2)SO(4). The optimized S dose of each fertilizer was later tested in second experiment to determine its role in improving drought tolerance of maize plants. A marked effect of S fertilization was observed on biomass accumulation and nutrients uptake in maize. In addition, the optimized doses significantly increased the gas exchange characteristics and activity of antioxidant enzymes to improve yield of maize. Among various S sources, application of K(2)SO(4) resulted in maximum photosynthetic rate (43%), stomatal conductance (98%), transpiration rate (61%) and sub-stomatal conductance (127%) compared to no S supply. Moreover, it also increased catalase, guaiacol peroxidase and superoxide dismutase activities by 55, 87 and 65%, respectively that ultimately improved maize yield by 33% with respect to control under water deficit conditions. These results highlight the importance of S fertilizers that would likely be helpful for farmers to get better yield in water deficient soils.